THE ANTIBACTERIAL EFFECT OF KASTURI LEAF EXTRACT (Mangifera casturi) AGAINST THE GROWTH OF Streptococcus mutans - Naila Khairiyah; Didit Aspriyanto; Deby Kania Tri Putri (Universitas Lambung Mangkurat, 2019)
ABSTRACTBackground: Dental caries is a common problem of teeth and mouth. Dental caries is caused by a complex biological interaction between acidogenic bacteria, fermented carbohydrates and host factors, such as teeth and saliva. Streptococcus mutans is known as one of the main bacteria that causes dental caries. Kasturi leaf extract (Mangifera casturi) has secondary metabolite compounds, such as alkaloids, terpenoids, flavonoids, phenolics and saponins which are efficacious as antibacterial. Objective: The aim of this study was to analyzing the effectiveness of antibacterial kasturi leaf extract (Mangifera casturi) against the growth of Streptococcus mutans bacteria. Method: This study was true experimental research with randomized pretest-posttest with control group design with 8 treatment groups consisted of kasturi leaves extract (concentration with 20 mg/ml, 25 mg/ml, 30 mg/ml, 35 mg/ml, 40 mg/ml and 45 mg/ml), positive control (chlorhexidine 0.2%) and negative control (aquades). Each treatment was repeated three times. Testing was done by liquid dilution method to determine the Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC). The data were analyzed using One Way Anova 95% (α=0.05) followed by Post hoc LSD for MIC data and Dunnet T3 for MBC data. Results: Based on the results of the analysis, it was known that Kasturi leaf extract had antibacterial effectiveness against the growth of Streptococcus mutans bacteria with MIC obtained at a concentration of 20 mg/ml and MBC obtained at 40 mg/ml. Conclusion: Kasturi leaf extract has an antibacterial effect against the growth of Streptococcus mutans. Key words: Antibacterial, kasturi leaf extract (Mangifera casturi), MIC, MBC, Streptococcus mutans